STUDI LESI MAKROSKOPIS DAN MIKROKOPIS PADA AYAM BROILER YANG DIINFEKSI VIRUS NEWCASTLE DISEASE VIRULEN ISOLAT ND-MHW/SLTG/2010 - PUSPITA, AGNISA NUR; Asmara, Widya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Newcastle disease (ND) is one of the diseases that cause significant economic losses due to the nature of the disease with high mortality in poultry especially in commercial poultry. This study aims to determine the organ lesions in broiler chickens macroscopic and microscopic infected by virulent ND virus isolates ND-MHW/SLTG/2010. A total of 6 chickens were kept without vaccination by the age of 14 days and then infected with 0.5 ml of virus isolates in intratrachealis ND-MHW/SLTG/2010 when chicken was 17 days. Six number of broiler chickens is without treatment used as a negative control. Four days after the infection, one of the chickens that showed clinical symptoms ND were necropsed to observe the macroscopic finding in infected chicken. Cerebrum, trachea, proventriculus, intestinum and lung histopathology were taken and made preparations for microscopic examination with Hematoxylin and eosin staining (H & E). Reidentification ND virus is a virus suspension of scouring the lung that have been infected chicken isolates ND-MHW/SLTG/2010. ND virus suspension was then inoculated at 10 days old TAB. TAB showing the death of the embryo after 2 days stored in the refrigerator, then collected and carried reidentification allantois fluid using hemagglutination assay (HA) and hemagglutination inhibition (HI) with the specific serum anti-ND. Macroscopic lesions were observed on the hemoraghi necrotic intestine, petechial hemoraghi proventriculus and congestion in the trachea, lung hemoraghi and meninges. Based on the histopathological picture of the proventriculus showed necrotic foki hemoraghi. Hemoraghi the trachea. Intestinum showed necrotic and hemoraghi Foki mucosa, villi shortened. Found kuffing perivascular lymphocytic and vakuolisasi the cerebrum. Hemagglutination test results show positive results that the formation of aggregates as dashed to pieces erythrocytes indicates this virus capable hemagglutination erythrocytes is one of the characteristics of the Newcastle virus. The results of hemagglutination inhibition test positive with specific serum agglutination ND formation or erythrocyte sedimentation means that the virus is actually a virus Newcastle.